A comprehensive approach to providing services to survivors of sexual and gender-based violence in Democratic Republic of Congo: addressing more than physical trauma. Issue 5 (4th July 2017) - Bennett, Cudjoe; Banda, Manka; Miller, Lior; Ciza, Joseph; Clemmer, William; Linehan, Mary; Sthreshley, Larry
ABSTRACT: The eastern Democratic Republic of Congo (DRC) is impacted by a prolonged conflict and humanitarian crisis. Sexual and gender-based violence (SGBV) affects an estimated 39.7% of women and 23.6% of men in the region, and is associated with serious medical, psychological, and socio-economic outcomes for survivors and communities. IMA World Health, a faith-based non-profit organisation, implements a USAID-funded project, Ushindi, which is a collaborative effort with three national NGOs and one technical partner in response to SGBV in eastern DRC. The consortium provides a comprehensive package of services to SGBV survivors, focusing on medical, emotional, psychological, legal, and socio-economic needs.